Analisis Penerapan Sistem Informasi Akuntansi Penjualan Pada CV. Advertising Arjuna Pematang Siantar - Buana, Arief Wira; Harmain, Hendra; Rahamani, Nur Ahmadi Bi (Universitas Labuhanbatu, 2023)
The purpose of this study was to determine the extent to which the application of the Sales Accounting Information System at CV Advertising Arjuna Pematang Siantar. This study used descriptive qualitative method. The type of data used in this research is primary and secondary data. Data collection techniques through observation, interviews, literature studies, and documentation. The informants in this study were Mrs. Sartika Pratiwi Arion, S.H, the owner of CV Advertising Arjuna Pematang Siantar and employees of CV Advertising Arjuna Pematang Siantar. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the application of the Sales Accounting Information System and the catalog available at CV Advertising Arjuna Pematang Siantar has not run optimally because it still uses a manual bookkeeping system and applies a catalog only for one product.Soit is better to use Software-Accounting so that the system used can run more effectively and efficiently and the available catalogs are immediately leveled for all products so that consumers' purchasing power for available products increases.